Peran Mediasi Hedonism Pada Hubungan Live Streaming E-Commerce dengan Perilaku Pembelian Impulsif - Syafiqoh, Siti Minhatus; Sutanto, Himawan Arif (EconBank: Journal of Economics and Banking, 2025)
The presence of live streaming features in e-commerce makes it easier for individuals to do online shopping with attractive offers and can create stimuli to meet emotional needs and impulse buying behavior. This study aims to analyze the effect of e-commerce live streaming on impulse buying behavior with the mediating role of hedonism. 100 users of live streaming e-commerce were taken as samples with purposive sampling. The data analysis technique in this study used PLS-SEM. The results showed that Live Streaming e-commerce has an effect on impulse buying behavior through customer hedonism. However, directly Live streaming e-commerce has no effect on impulse buying behavior. While Hedonism has a positive effect on impulse buying behavior.